Possibilities of Using Endoscopic Equipment in the Treatment of Post-Traumatic Urethral Strictures in Children - D.V. Shevchuk (Zaslavsky O.Yu., 2016)
Background. Damage to the urethra in damaged pelvic bones in children is marked less than in adults (less than 1 %) (Tarman G.J. et al., 2002). Post-traumatic urethral stricture in children is a quite rare and complex urologic pathology. Due to anatomical features, treatment for urethral stricture in children is different from its treatment in adults (Onen A. et al., 2005; Nerli R.B. et al., 2008; Ranjan P. et al., 2011). M.M. Koraitim (2012) described the experience of treating 20 patients with complications after transperyneal urethral plasty. The author noted that in the absence of need for reconstruction of the bladder neck, it is quite effective to use endoscopic incision of urethral stricture. T.E. Helmy, A.T. Hafez (2013) also described the results of the successful application of endoscopic equipment (direct visual urethrotomia) after open urethroplasty. The important point that leads to finding effective minimally invasive treatments for post-traumatic urethral strictures in children is the development of erectile dysfunction in the future, the incidence of which, according to some authors, (Koraitim M.M., 2014) is up to 47 %. The aim of the study: based on the available published data and own treatment outcomes in children with posterior urethral strictures, to establish the role of endoscopic treatment of this complex pathology as a method of prevention and treatment of neuromuscular dysfunction of the bladder. Materials and methods. At the premises of the surgical departments of Zhytomyr Regional Children's Clinical Hospital, there were widely implemented invasive endoscopic methods for the diagnosis and treatment of pathologies of the lower urinary tract. Available equipment enables to carry out diagnostic procedures from 1 month old. A variety of endoscopic surgeries on the lower urinary tract is being performed, namely - the removal of calculi, incision of valves and strictures of the posterior urethra, dissection of urethral cysts and ectopic ureterocaele, etc. Also in 2010, the first attempt was made to remove a calculus from the posterior urethra by means of percutaneous 3-port cystoscope. From 2013, the treatment of post-traumatic strictures of the posterior urethra began using endoscopic control. Results. The article presents the results of a successful minimally invasive treatment using modern endoscopic equipment in two patients with post-traumatic posterior urethral strictures. A special attention was paid to the effectiveness of the method in the diagnosis and treatment of neuromuscular dysfunction of the bladder in these patients. Conclusions. Consequently, the use of minimally invasive modern equipment not only makes it possible to effectively diagnose the damage to lower urinary tract, but also can be an effective mechanism for low-impact surgery at short post-traumatic urethral strictures in children. Timely adequate treatment of scar urethral strictures in children will minimize the incidence of infravesical obstruction and violation of the evacuation function of the bladder with the development of its neuromuscular dysfunction.